Monetary valuation of COVID-19 informal care: caregivers’ willingness to pay and willingness to accept - Vajiheh Ramezani-Doroh; Faride Karimi; Maryam Rangchian; Yadolah Hamidi (Cost Effectiveness and Resource Allocation, 2023)
Abstract Background Informal care can reduce hospitalization frequency and time, elevate bed turnover, and increase the health systems' capacity. This type of care has shown meaningful value in managing many cases through the COVID-19 pandemic. The present study aimed to identify determinants of monetary valuation of informal care and the burden of this care on the COVID-19 patients’ caregivers. Methods Through a cross-sectional phone survey from June to September 2021 in Sanandaj city, the west of Iran, COVID-19 patients and their caregivers (Each Group No. 425) were separately interviewed. A simple probabilistic sampling method was applied. Two questionnaires were developed and used after validation. Monetary valuation of informal caregivers was done using Willingness to pay (WTP) and willingness to accept (WTA). Double hurdle regressions were used to determine related variables to WTP/WTA. R software was used for the data analysis. Results The total mean (Standard Deviation) of WTP and WTA were $12.02(28.73), $10.30(15.43) USD. Most respondents put a zero value on informal care by WTA (243(57.18%) and WTP [263 (61.88%)]. Caregivers’ Employment, and being spouse/child of the care recipient increased the probability of reporting a positive value for WTP (p-value < 0.0001, p-value = 0.011 respectively) and WTA (p-value = 0.004, p-value < 0.0001 respectively). An increase in the number of caring days decreased the probability of reporting positive WTA (p-value = 0.001) and increased the mean of lnWTP (p-value = 0.044). Perceived difficulty in doing indoor activities and perceived difficulty in doing outdoor activities decreased lnWTA mean (p-value = 0.002) and lnWTP mean (p-value = 0.043) respectively. Conclusions Increasing caregivers’ self-efficacy and facilitating their involvement in the caring process could be facilitated through flexible work status, educational programs, and interventions on decreasing their burnout.